INTELLECTUAL COGNITIVE DEVELOPMENT OF RILEY’S CHARACTER IN INSIDE OUT (2015): A CHILD PSYCHOLOGY STUDY - Rizki Dyah Koes Novitasari; Teguh Kasprabowo (Dinamika Bahasa dan Budaya, 2022)
Abstract The purpose of this paper is to identify Riley’s cognitive development and the factors that influence the process. Riley was the main character of Pete Docter’s movie: “Inside Out” where the researcher took data from. This is an animated movie that describes the development process and way of thinking of every human being so that it will form a character and action. In this qualitative study, the researcher used the Psychology of The Child theory by Jean Piaget (1969). The data used in this study is a movie script and the movie. The researcher found that the main character, Riley Andersen, has several stages of cognitive development based on her actions and experiences. Furthermore, there are factors that influence the cognitive development process in Riley. Finally, the researcher found four stages and factors that influence Riley’s cognitive development process. The process of cognitive development can be seen from Riley’s actions when she was born until she grew as a good child. Keywords: Child psychology, Jean Piaget Psychology of The Child, Cognitive Development, The Stages of Cognitive Development